CH4/CO2 Ratios and Carbon Isotope Enrichment Between Diet and Breath in Herbivorous Mammals - Cerling, Thure E.; Bernasconi, Stefano M.; Hofstetter, Lino S.; Jaggi, Madalina; Wyss, Fabia; Rudolf von Rohr, Claudia; Clauss, Marcus (Frontiers in Ecology and Evolution, 2021)
Breath and diet samples were collected from 29 taxa of animals at the Zurich and Basel Zoos to characterize the carbon isotope enrichment between breath and diet. Diet samples were measured for 13C and breath samples for CH4/CO2 ratios and for the respired component of 13C using the Keeling plot approach. Different digestive physiologies included hindgut coprophagous, hindgut non-coprophagous, foregut non-ruminants, and foregut ruminants. Isotope enrichments from diet to breath were 0.8±0.9‰, 3.5±0.8‰, 2.3±0.4‰, and 4.1±1.0‰, respectively. CH4/CO2 ratios were strongly correlated with isotope enrichments for both foregut and hindgut digestive strategies, although CH4 production was not the sole reason for isotope enrichment. Average CH4/CO2 ratios per taxon ranged over several orders of magnitude from 10-5 to 10-1. The isotope enrichment values for diet-breath can be used to further estimate the isotope enrichment from diet-enamel because Passey et al. (2005) found a nearly constant isotope enrichment for breath-enamel for diverse mammalian taxa. The understanding of isotope enrichment factors from diet to breath and diet to enamel will have important applications in the fields wildlife ecology, animal physiology, and in paleontology.